Maternity Nurses’ Performance Regarding Cardiopulmonary Resuscitation During Pregnancy: Simulation Based Intervention (International Journal of Studies in Nursing, 2018)
Background: Training maternity nurse regarding cardiopulmonary resuscitation during pregnancy is most important for properly care of such emergency situations during pregnancy and save woman’s and fetal lives.The aim of the present study was to evaluate effect of simulation-based intervention on maternity nurse’ performance regarding cardiopulmonary resuscitation during pregnancy. Design Aquasi-experimental design was adopted in the current study.The study was conducted at woman’s health nursing department training lab at faculty of nursing affiliated at Benha University Hospital. Where a lot of women are admitted for normal and vaginal delivery, gyneacological treatment and surgery. Subjects: A Convenient sample of a total 52 maternity nurses was included. Tools: Two tools: Were used for data collection. Interviewing questionnaire sheet was concerning with nurses personnel characteristics’ and knowledge regarding cardiopulmonary resuscitation during pregnancy and performance check list sheet.the result of the present study that there was a highly statistical difference between knowledge and practical scores of maternity nurse at pre and post intervention. The study concluded that the simulation bases intervention is highly improved maternity nurses’ performance regarding cardiopulmonary resuscitation during pregnancy. The present study recommended that simulation-based training regarding cardiopulmonary resuscitation should be provided for all obstetrics health care givers.